Integrasi Pesantren dan Sekolah (Kajian atas Pemikiran Abdurrahman Wahid) - Herman Wicaksono (Pendidikan Agama Islam, 2022)
Pesantren and schools should be integrated to the point where they both need to work together to improve the quality of education in Indonesia. Aside from the benefits and drawbacks of the pesantren education model, Abdurrahman Wahid, the